The Relationship of Proinflammatory and Antiinflammatory Adipokines in the Development of Metabolic Syndrome in Centrally Obese Men - Anna Meiliana; Andi Wijaya; Suryani As'ad (The Prodia Education and Research Institute (PERI), 2010)
BACKGROUND: The increased prevalence of obesity worldwide is correlated with increasing prevalence of metabolic syndrome. Studies of adipose tissue have been improved from an inert energy storage to a metabolic active endocrine organ. Adipokines secreted by this tissue play a role in maintaining metabolic homeostasis. The large mass of visceral fat tissue causing the imbalance of these adipokines leading to metabolic abnormality known as the metabolic syndrome (MetS). This study was performed to understand relationship of proinflammatory adipokines (resistin, TNF-α, RBP4 and visfatin) and anti-inflammatory adipokines (adiponectin and vaspin) in the development of MetS.METHODS: This was a cross-sectional study using 122 central obesity men with waist circumference >90 cm, age from 30–60 years old. Proinflammatory adipokines (resistin, TNF-α, RBP4 and visfatin) and anti-inflammatory adipokines (adiponectin and vaspin) was measured by ELISA method.RESULTS: The crosstab study showed that subjects who have >2 high proinflammatory adipokines (17.3%) has higher MetS prevalence (OR = 1.16; p = 0.72) compare to subjects with <2 high proinflammatory adipokines (14.8%), subjects with low anti-inflammatory adipokines profile (18.9%) has higher prevalence of MetS (OR=1.38; p=0.22) compare to subjects with high anti-inflammatory adipokines (13.7%) and the prevalence of MetS became 1.49 times higher (p=0.24) when we combine the high RBP4 and low adiponectin profile (21.1%) compare to subjects with low RBP4 and high adiponectin (14%).CONCLUSIONS: This study showed that each adipokine was not strong enough to induce MetS, so the interaction between proinflammatory and antiinflammatory adipokines were needed to induce a systemic metabolic abnormality. Thus, the adipokines equilibrium was important to prevent MetS especially in centrally obese subjects.KEYWORDS: obesity, metabolic syndrome, adipokines, resistin, TNF-α, RBP4, visfatin, adiponectin, vaspin